2014
DOI: 10.1063/1.4900759
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear model for magnetoacoustic waves in dense dissipative plasmas with degenerate electrons

Abstract: The properties of nonlinear fast magnetoacoustic waves in dense dissipative plasmas with degenerate electrons are studied theoretically in the framework of the Zabolotskaya-Khokhlov (ZK) equation for small but finite amplitude excitations. Shock-like solutions of the ZK equation are obtained and are applied to parameters relevant to white dwarf stars

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…1999; Masood et al. 2014). Careful application of these equations and similarities allow experiments to be scaled to astrophysical phenomena that have spatial and temporal scales that are greater by as much as 15–20 orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1999; Masood et al. 2014). Careful application of these equations and similarities allow experiments to be scaled to astrophysical phenomena that have spatial and temporal scales that are greater by as much as 15–20 orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…2008; Masood et al. 2014). It is pertinent to mention here that when the laser hits a solid target, fast electrons are produced and such a non-thermal population plays an important role in inertial confinement fusion by fast ignition (Tabak et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low frequency magnetosonic solitons are investigated in a magnetized spin-1/2 degenerate plasma, while opting for the Sagdeev potential approach (Marklund, Eliasson & Shukla 2007), where the authors found that rarefractive magnetosonic solitons may exist due to a balance between nonlinearities and the quantum diffraction term. Nonlinear magnetosonic waves in quantum dissipative magnetized plasmas are investigated in Masood et al (2014). Linear and weak nonlinear propagation of magnetosonic waves in a degenerate plasma using perturbation theory was formulated in Haas & Mahmood (2018), modified KdV was derived having coefficients which are a strong function of quantum effects.…”
Section: Introductionmentioning
confidence: 99%
“…[9]. Nonlinear magnetosonic waves in dense dissipative magnetized plasmas have also been studied using reductive perturbation techniques, leading to the derivation of a Zabolotskaya-Khoklov equation [10].…”
Section: Introductionmentioning
confidence: 99%